(untitled) (CIPEEX, 2024)
ALTHOUGH RARE, MALE BREAST CANCER CAN ALSO AFFECT INDIVIDUALS. IN 2020, THE NATIONAL CANCER INSTITUTE (INCA) RECORDED 207 DEATHS OF MEN DUE TO THE DISEASE, DRAWING THE ATTENTION OF THE SCIENTIFIC COMMUNITY. IT IS BELIEVED THAT THE ETIOLOGY OF MALE BREAST CANCER (MBC) IS RELATED TO GENETIC AND EXTERNAL FACTORS SUCH AS HORMONAL TREATMENTS, PROLONGED EXPOSURE TO RADIATION IN THE THORACIC REGION, OBESITY, AND ALCOHOLISM. CONSIDERING THE SERIOUSNESS OF THIS TYPE OF NEOPLASM, EARLY DIAGNOSIS AND THERAPEUTIC MEASURES SHOULD BE TAKEN, ADDRESSING THE INDIVIDUAL AS A WHOLE, THUS ENABLING A BETTER PROGNOSIS, REHABILITATION, AND QUALITY OF LIFE. THE STUDY’S OBJECTIVE IS TO ANALYZE THE CLINICAL ASPECTS OF MALE BREAST CANCER. THIS STUDY IS A LITERATURE REVIEW IN THE INTEGRATIVE MODALITY. THE DESCRIPTORS "BREAST CANCER," "MEN," AND "PATHOLOGY" WERE APPLIED TO THE DATABASES SCHOLAR GOOGLE, SCIELO, PUBMED, AND INCA. FIFTY-SIX ABSTRACTS WERE EXAMINED, WITH INCLUSION CRITERIA OF THE PERIOD FROM 2010 TO 2023, STUDY TYPE, AND LANGUAGE. THUS, 21 ARTICLES WERE SELECTED. REGARDING THE DIAGNOSIS OF MBC, SELF-EXAMINATION IS THE PATIENTS’ GREATEST ALLY FOR EARLY DETECTION. THIS MEANS THAT BREAST CANCER IN MEN ALSO REQUIRES PREVENTIVE MEASURES, SUCH AS PERFORMING CYTO AND HISTOPATHOLOGICAL EXAMINATIONS. MALE BREAST CANCER GENERALLY AFFECTS INDIVIDUALS OF WHITE ETHNICITY, ABOVE THE AGE OF 60, AND HAS A PREFERENTIAL LOCATION BEHIND THE AREOLA, POTENTIALLY IN BOTH BREASTS, WITH A DIAMETER RANGING FROM 1.5–17 CM. THE PREDOMINANT HISTOLOGICAL TYPE IS INVASIVE DUCTAL CARCINOMA, WITH MODERATE HISTOLOGICAL GRADE BEING THE MOST FREQUENT, FOLLOWED BY CASES DIAGNOSED AT STAGES III AND IV, REPRESENTING ADVANCED TUMORS. AS FOR METASTATIC PATTERNS, THE MOST COMMON SITES OF PROLIFERATION ARE THE BONES, LUNGS, AND LIVER. REGARDING TREATMENT, THE MAJORITY UNDERGO SURGICAL TREATMENT WITH RADICAL MASTECTOMY AND RECEIVE RADIOTHERAPY, CHEMOTHERAPY, AND HORMONE THERAPY AS ADJUVANT THERAPIES. ACCORDING TO MASTOLOGICAL STUDIES, THE 5-YEAR OVERALL SURVIVAL (OS) IS ON AVERAGE 75%. THEREFORE, IT IS CONCLUDED THAT THERE IS A NEED TO ENGAGE THE MALE POPULATION IN PREVENTIVE MEASURES TO ACHIEVE EARLIER TUMOR DETECTION FOR A BETTER PROGNOSIS, RAPID IMPLEMENTATION OF TREATMENT, AND COMPREHENSIVE MONITORING OF MEN’S HEALTH TO FACILITATE PHYSICAL AND EMOTIONAL REHABILITATION IN THE FIGHT AGAINST THE DISEASE.